Depression and Coping Styles of College Students in China During COVID-19 Pandemic: A Systemic Review and Meta-Analysis - Guo, Shengyu; Kaminga, Atipatsa Chiwanda; Xiong, Jie (Frontiers in Public Health, 2021)
Background: The rapid spread and uncertain outcome of the 2019 novel coronavirus disease (COVID-19) around the world have caused worry, fear, and stress among the general population. Nevertheless, the prevalence of depression among college students in China during lockdown, following the COVID-19 pandemic, and their coping strategies have not been quantitatively assessed. Objective: We aimed to evaluate the prevalence of depression among college students in China during the lockdown due to the COVID-19 pandemic and assess their coping strategies. Methods: Systematic review and meta-analysis were conducted to assess the prevalence of depression among college students in China and their coping strategies. Results: The results indicated that, during lockdown in the COVID-19 pandemic, the prevalence rates of college students in China suffering from mild, moderate, and severe depression were 25% (95% CI = 17–33%), 7% (95% CI = 2–14%), and 2% (95% CI = 1–5%), respectively. Besides, the proportion of college students who use WeChat and Weibo to acquire COVID-19 knowledge was 39% (95% CI = 13–68%), whereas the proportion of college students using mental health application services (APPs) to deal with depression was 59% (95% CI = 41–73%). Conclusions: The prevalence of depression among college students in China was high during the lockdown in the COVID-19 pandemic. Thus, considering the adverse outcomes of depression, it is imperative to screen college students in China for depression during the CIVID-19 pandemic and provide them with necessary psychological interventions to control and prevent depression. Social media platforms, such as WeChat and Weibo, and mental health APPs could provide an opportunity for psychological health information dissemination for college students. However, their effectiveness in reducing depression will have to be assessed.